Underpricing and aftermarket performance of IPOs during the Covid-19 period: Evidence from Istanbul stock exchange - Metin İlbasmış (Borsa İstanbul Review, 2023)
The effect of uncertainty on IPO underpricing, short-term performance after IPO, and hot-and-cold-IPO market cycles have received a great deal of attention in the literature. This study revisits these issues of IPO activities under the Covid-19 pandemic with a focus on the Turkish IPO market. Measuring the underpricing and aftermarket performance of IPOs based on the cumulative abnormal returns of the first, second, third, fourth, fifth, tenth, and twenty-first days, we examine how underpricing and aftermarket performances are influenced by Covid-19 and some uncertainty proxies, such as some company characteristics (age, total assets), offering characteristics (gross proceeds, IPO price risk), and aftermarket variables (first-day trading volume, standard deviation of stock prices after the IPO) after controlling for firm, industry and market level variables (first-day trading value, the portion of the firm offered to public, price-earnings ratio, dummy variables for technology, manufacturing, and financial institutions sectors, standard deviation of a market index, moving average return of a market index). The study documents that while an IPO launched during the Covid-19 period has larger underpricing, an average IPO firm that is older, has more assets, generates larger proceeds, trades more on its first day of trading, is expected to fluctuate less after the IPO has a smaller underpricing at its initial public offering. Empirical results show that short-term market-adjusted abnormal returns of IPO firms during the pandemic are much larger than those before the pandemic.
Keywords: G14; G18; G32; H12; 330; Initial public offerings; Short-term performance; IPO Underpricing; Uncertainty; Covid-19